Collaboration of Urban and Rural Mainstream Schools with Special Education Facilities - Zenon Stanisław Gajdzica; Magdalena Bełza-Gajdzica (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Introduction: Improving the quality of inclusive education is determined by many factors. One of them, applied in many countries, is the support for mainstream schools by building a partnership with special schools and by making use of their resources. The article is focused on the issue of cooperation between mainstream schools and special ones, viewed from the standpoint of the staff of the former. What has been additionally undertaken is the examination of this partnership as regards the (rural and urban) environment of mainstream school. Research Aim: The studies were aimed at recognizing the forms of collaboration between mainstream and special schools comprised in the declarations of mainstream school staff, as well as specifying the relationship between the intensity of collaboration indications and the (rural and urban) location of mainstream schools. Method: The studies were conducted with the use of diagnostic poll method. The data were collected with the use of a questionnaire for the staff of mainstream primary schools. For the needs of this article, the issue was analysed of good practices applied to build the inclusive culture of school. 2548 answers were obtained (1498 from rural and 1046 from urban schools, in 4 cases the location was not provided so these facilities were excluded from the research). From all the answers, the declarations were selected which concerned the cooperation of mainstream schools with special ones. Results: An analysis of the data revealed a meagre level of cooperation. Only 2.01% of urban and 1.87% of rural schools declared different forms of collaboration with special facilities. They mostly concerned the common organizing of integration events. The (rural / urban) environment practically does not differentiate the level of cooperation. Conclusions: The building of cooperation (which, in the light of the analysed expert literature, is beneficial to both types of school) requires some systemic solutions that initiate various forms of partnership and the creation of a set of stimuli (e.g. in the form of projects) encouraging to regular cooperation.